Depression, Rumination, and Impulsive Action: A Latent Variable Approach to Behavioral Impulsivity. Issue 8 (17th November 2021) - Hasegawa, Akira; Somatori, Keita; Nishimura, Haruki; Hattori, Yosuke; Kunisato, Yoshihiko
Abstract: Previous research on the relationship between rumination and behavioral impulsivity has been limited because impulsivity was assessed by using individual tasks. This study examined the concurrent associations of a latent variable named impulsive action with rumination and depression to alleviate the task-impurity problem and the low reliability of laboratory tasks assessing impulsivity. This study also examined whether stressors mediated the association between impulsive action and rumination. University students in Japan ( N = 176) conducted three laboratory tasks assessing impulsive action: the Go/No-Go Task, the Stop Signal Task, and the Conners Continuous Performance Test 3rd Edition. They also completed self-report measures of rumination, stressors, and depression. Results indicated that the latent variable named impulsive action constructed from the performance in these three tasks was positively associated with rumination. Moreover, stressors mediated this association. Also, impulsive action was positively associated with depression via the increase in stressors and rumination. These findings and those of previous studies examining associations between rumination and self-reported impulsivity suggest that impulsivity might be a determinant of rumination.